The type 2B p.R1306W natural mutation of von Willebrand factor dramatically enhances the multimer sensitivity to shear stress. (12th September 2013) - Scaglione, G. L.; Lancellotti, S.; Papi, M.; De, M.; Maiorana, A.; Baronciani, L.; Pagliari, M. T.; Arcovito, A.; Di, E.; Peyvandi, F.; De, R.
Summary Background Shear stress triggers conformational stretching of von Willebrand factor (VWF), which is responsible for its self‐association and binding to the platelet receptor glycoprotein (GP)Ibα. This phenomenon supports primary hemostasis under flow. Type 2B VWF natural mutants are considered to have increased affinity for platelet GPIbα. Objectives To assess the mechanism responsible for the enhanced interaction of the p.R1306W VWF mutant with the platelet receptor. Methods The interaction of GPIbα with wild‐type (WT) and p.R1306W VWF multimers and A1–A2–A3 constructs was investigated with surface plasmon resonance spectroscopy. Analysis of the static VWF conformation in solution was performed with dynamic light scattering spectroscopy. The shear stress‐induced self‐association of VWF multimers was investigated with atomic force microscopy (AFM) over a 0–60 dyn cm−2 range. Results WT VWF did not interact with GPIbα under static conditions, whereas the mutant at ~ 2 μg mL−1 already bound to the receptor. By contrast, the WT and p.R1306W‐A1–A2–A3 constructs showed comparable affinities for GPIbα (Kd ~ 20 nm). The hydrodynamic diameter of resting R1306W VWF multimers was significantly greater than that of the wild type (210 ± 60 nm vs. 87 ± 22 nm). At shear forces of < 14 dyn cm−2, the p.R1306W multimers rapidly changed conformation, entering a regime of self‐aggregation, which, in contrast, was induced for WT VWF by shear forces of > 30 dyn cm−2. Mechanical stretching AFM experiments showed that p.R1306W multimers needed less energy per length unit (~ 10 pN) to be stretched than the WT protein. Conclusions The increased affinity of p.R1306W VWF for GPIbα arises mostly from higher sensitivity to shear stress, which facilitates exposure of GPIbα binding sites.